Two Types of Cation Channel Activated by Stimulation of Muscarinic Receptors in Guinea-Pig Urinary Bladder Smooth Muscle - Masayuki Yamamoto; Toshihiro Unno; Hayato Matsuyama; Masanobu Kohda; Noriyuki Masuda; Masakazu Nishimura; Toshiaki Ishii; Seiichi Komori (Elsevier, 2008)
The present study, aiming to elucidate ion channel mechanisms underlying muscarinic receptor-induced depolarization, has characterized membrane currents induced by carbachol in single guinea-pig urinary bladder myocytes. Application of carbachol to cells that were voltage-clamped at − 50 mV produced an atropine-sensitive, biphasic inward current consisting of an initial peak followed by a smaller sustained phase. Replacing the extracellular Na+ and intracellular Cl− with impermeable tris+ and glutamate−, respectively, demonstrated that the biphasic current is entirely composed of cation currents. Its initial peak phase was abolished by buffering intracellular Ca2+ to a constant level of 100 nM or depleting intracellular Ca2+ stores, and it was mimicked by the Ca2+ releaser caffeine. Ca2+ entry evoked by voltage steps in the sustained phase induced no noticeable change, indicating that this phase of cation current is insensitive to a rise of [Ca2+]i. These results demonstrate that muscarinic receptor stimulation invokes the openings of two types of cation channel, a Ca2+-activated and a receptor-operated type; the former channels are gated by a rise in [Ca2+]i upon intracellular Ca2+ release, and the latter are gated through other muscarinic receptor-coupled signal transduction mechanisms. Keywords:: cation channel, muscarinic receptor, carbachol, bladder smooth muscle, guinea pig